1998
DOI: 10.1097/00005392-199812010-00014
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL ROLE OF REL/NUCLEAR FACTOR-kappa B IN THE PATHOGENESIS OF INTERSTITIAL CYSTITIS

Abstract: The fact that NF-kappaB is capable of transactivating pro-inflammatory mediators, which in turn can amplify NF-kappaB activation by a positive regulatory loop, suggests that inflammatory and/or immune responses in interstitial cystitis can be exacerbated possibly by persistent activation of this nuclear factor. We believe that our study provides a novel basis for investigating the role of NF-kappaB activation in the pathophysiology of interstitial cystitis and further opens a frontier for the development of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Moreover, our results are in accordance with experimental data in a panel of human bladder UC cell lines with varying metastatic potential indicating that highly metastatic bladder UC cells constitutively expressed high levels of NF-κΒ, in comparison to that of cells with low metastatic potential [22]. In addition, the role of the NF-κΒ protein in bladder UC tumourigenesis has previously been speculated because of its relationship with interstitial cystitis [2], given that the development of bladder cancer is related to urinary tract infection [30,52]. Thus, NF-κB is more often activated in urothelial cells from interstitial cystitis as compared to controls [2].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, our results are in accordance with experimental data in a panel of human bladder UC cell lines with varying metastatic potential indicating that highly metastatic bladder UC cells constitutively expressed high levels of NF-κΒ, in comparison to that of cells with low metastatic potential [22]. In addition, the role of the NF-κΒ protein in bladder UC tumourigenesis has previously been speculated because of its relationship with interstitial cystitis [2], given that the development of bladder cancer is related to urinary tract infection [30,52]. Thus, NF-κB is more often activated in urothelial cells from interstitial cystitis as compared to controls [2].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the role of the NF-κΒ protein in bladder UC tumourigenesis has previously been speculated because of its relationship with interstitial cystitis [2], given that the development of bladder cancer is related to urinary tract infection [30,52]. Thus, NF-κB is more often activated in urothelial cells from interstitial cystitis as compared to controls [2]. Perhaps, the most intriguing finding of our study was the fact that p65/RelA nuclear overexpression connotes a poor survival probability and remains a prognostic factor after multivariate analysis in both superficial and muscleinvasive UCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on the pathophysiology of IC, three mechanisms are extensively studied: mucosal dysfunction, mast cell activation and neuroimmune mechanism. Recent studies have reported that the inflammatory and/or immunologic responses in IC may be a result of NFjB activation and that NF-jB can be reduced with treatment [22][23][24]29]. Although there are several mediators that may increase the levels of NF-jB in IC, the death ligand TRAIL, a recently discovered member of TNF (tumor necrosis factor) family, and evidences that TRAIL may be a further factor that stimulates NF-jB suggest that this ligand may also be [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Current theories on the pathogenesis of IC include mucosal permeability, increased mast cell activation and neuroimmune mechanisms [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Recent investigations have reported that the inflammatory and/or immunologic responses in IC may be a result of NFjB (nuclear factor-{kappa}B) activation and that NFjB can be reduced with treatment [22][23][24]. Although there are several mediators that may increase the levels of NF-jB in IC, the death ligand TRAIL (TNFrelated apoptosis-inducing ligand) family, a recently discovered member of TNF (tumor necrosis factor) and evidences that TRAIL may be a further factor that stimulates NF-jB suggest that this ligand may also be involved in IC [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…It appears to be a crucial factor in patients with intestinal cystitis, as revealed by its presence, pattern and distribution in biopsies. 84 The NF-B pathway has proved vital in ischaemia-reperfusion brain injury, which initiates the inflammatory response involving IL-6 and ICAM-1. 21 Conditions such as heat stress 85 and exposure to xenobiotics, for example diesel exhaust particles, 86 have further been reported to alter the IKK/IB/NF-B pathway leading to tissue injury.…”
Section: Role Of Nf-b In Infection Inflammation and Cellular Stressmentioning
confidence: 99%